Community Perception and Expectations on Corporate Social Responsibility : A Comparative Case Study on Ambuja and ACC Limited - Kumari, Santosh; Sharma, Tanu; Sehrawat, Anil (Prabandhan: Indian Journal of Management, 2017)
The Indian cement industry, a potential polluter, has won numerous green awards for fulfilling its commitment towards sustainable community development. Companies today have integrated the community development goals into the business goals by considering responsibilities for the impact of their activities on all stakeholders as well as the environment. This paper analyzed the CSR practices adopted by Ambuja Cement Foundation & ACC in relation to local community and to measure the impact of these CSR practices on the community. For this purpose, the perceptions and expectations of the community about companies’ corporate social responsibility practices were considered and analyzed. The data was collected through interview of key executives responsible for implementation of CSR activities undertaken by these companies, and the data related to CSR activities towards the community was collected by conducting focus group discussions and with the help of a structured questionnaire.